Investigating the Effect of Future Orientation on Saving Intention of Generation Z’s University Students in Vietnam’s Northern Region - Do, Hoai Linh; Vu, Thi Mai Phuong; Nguyen, Van Giang; Vu, Ngoc Minh; Nguyen, Duc Trung; Tran, Thanh Vinh (International Journal of Business, Economics, and Social Development, 2023)
Young people are often thought to have a lifestyle focusing on enjoyment, which is why issues related to saving among the youth, especially saving money, receive significant attention from society. This issue has been analyzed in some previous studies; however, there is a new factor that has not been explored in the context of Vietnam, which is future orientation. The purpose of this study is to find out the relationship between future orientation, attitude towards saving and saving intention of generation Z university students in Northern Vietnam. The research method used was the combination of qualitative and quantitative methods. The primary data was collected from 531 respondents who are currently studying at universities in Northern Vietnam and the data was analyzed by using SPSS and AMOS software. The structural equation modeling (SEM) method was used, and the results indicate that both future orientation and attitude towards saving have a positive impact on savings intention. Furthermore, the mediating role of attitude in the relationship between future orientation and saving intention was confirmed. Therefore, the results should be applied by governmental agencies, financial organizations and individuals, especially young people, to encourage saving intention, and furthermore, saving behavior.